Identification of Bacterial Critical Points and Antibacterial Effect of Lactic acid on Beef Carcass - Rajeev K (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1994)
During the process of slaughter and subsequent processing, the beef carcass is exposed to bacterial contamination. Bacterial load is one of the parameters for assessment of the sanitary conditions in slaughter operations. It is tedious and time consuming to evaluate bacterial load of carcass surface as a whole. Therefore assessment of bacterial load on certain points (critical points) in the carcass which are more frequently exposed to contaminants will help in quick assessment of sanitaty standard. In the present study six critical points were selected on beef carcasses to evaluate the bacterial contamination. Carcasses from two slaughter houses differing in infrastructural facilities were used for this assessment and comparison. There was significant difference in the level of bacterial contamination on critical points of carcasses obtained from the two sources. Significant difference was noticed between points as well. Among the critical points, neck-lateral has shown highest level of contamination. This may be due to chances of exposure to contaminants during bleeding and flaying. The abdomen-medial was comparatively less contaminated.